The concept and characteristics of amnesty in Ukraine - Крайник, Г. С. (Problems of legality, 2014)
In this article the author analyzed the concept, characteristics of amnesty in Ukraine, considered the subjects taking the amnesty. Proposed changes to the Law of «On amnesty in Ukraine».